4
$\begingroup$

If $a,\;b,\;c$ are in Geometric Progression, then the equations $ax^2+2bx+c=0$ and $dx^2+2ex+f=0$ have a common root if $\;\displaystyle\frac da,\;\frac eb,\;\frac fc$ are in:

  1. Arithmetic Progression
  2. Geometric Progression
  3. Harmonic Progression

Considering the first equation as $a_1x^2+b_1x+c_1=0$ and the second one as $a_2x^2+b_2x+c_2=0$, I applied the condition for the common root of two quadratic equations, i.e, $$(a_1b_2-b_1a_2)(b_1c_2-c_1b_2)=(c_1a_2-a_1c_2)^2$$ However, it gives a large equation in terms of the constants and does not lead me anywhere near finding the relation.

$\endgroup$
1
$\begingroup$

HINT:

Let $$\frac cb=\frac ba=r\ne0\implies b=ar,c=ar^2$$

So, $ax^2+2bx+c=0\implies a(x^2+2rx+r^2)=0\implies x=-r$

$$\implies d(-r)^2+2e(-r)+f=0\implies r=\frac{e\pm\sqrt{e^2-df}}d$$

$\endgroup$
  • $\begingroup$ A shorter approach would be to divide $dr^2-2er+f$ by $ar^2$. $\endgroup$ – Aditya Agarwal Dec 9 '15 at 9:31
3
$\begingroup$

Hint: you haven't used the information that $a,b,c$ are in geometric progression. You can write $b=ar, c=ar^2$ and plug that into your condition, which simplifies it. You can also set $a=1$, which corresponds to dividing the original equation by $a$-if it is zero your equation is just $0=0$ You can plug the expression of each progression in for the second equation

If you continue to solve $x^2+rx+r^2=0$, you find the roots are proportional to $r$-so geometric progression clearly won't work as that says the two ratios are different.

$\endgroup$
2
$\begingroup$

For two quadratic equations, $\begin{cases}a_0x^2+b_0x+c_0=0\\a_1x^2+b_1x+c_1=0\\\end{cases}$, if the following determinant
$\begin{vmatrix} a_0&b_0&c_0&0\\ 0&a_0&b_0&c_0\\ a_1&b_1&c_1&0\\ 0&a_1&b_1&c_1\\ \end{vmatrix}$
vanishes, then there is indeed a common root for the two.

$\endgroup$
1
$\begingroup$

Do note that the discriminant of the first equation is $b^2-4ac$. Since a,b,c are in G.P, we must have $$b^2=ac$$ And we get the discriminant of the first quadratic to be 0. Hence $ax^2+2bx+c=0$ has equal roots. And since according to the question, $dx^2+2ex+f=0$ has a common root, it implies that both the quadratics are proportional to each other. $$dx^2+2ex+f=k(ax^2+2bx+c)$$ Finally comparing coefficients we get, $d=ak$,$2e=2bk$ and $f=ck$ and hence $$\frac da=\frac eb=\frac fc=k$$ this is the write ans

$\endgroup$
1
$\begingroup$

Hint:

Let $a=r^2c,b=rc$. The first equation is

$$(r^2x^2+2rx+1)c=(rx+1)^2=0.$$

The root is double, $x=-\dfrac 1r$ !

Then

$$\frac d{r^2}-2\frac er+f=0,$$ and $$c\frac da-2c\frac eb+c\frac fc=0,$$ and we have an arithmetic progression.

$\endgroup$
0
$\begingroup$

Using lab bhattarcharjee's method, $$d(-r)^2+2e(-r)+f=0$$ $$\therefore dr^2-2er+f=0$$Dividing throughout by $ar^2$, we get $$\frac da-\frac{2e}{ar}+\frac{f}{ar^2}=0$$$$\therefore \frac da+\frac{f}{c}=\frac {2e}{b}$$ Thus, $\displaystyle \frac da,\; \frac eb,\;\frac fc$ are in Arithmetic Progression.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.